Ultrafast Spin Dynamics in Photodoped Spin-Orbit Mott Insulator Sr2IrO4 - Afanasiev, D.; Gatilova, A.; Groenendijk, D. J.; Ivanov, B. A.; Gibert, M.; Gariglio, S.; Mentink, J.; Li, Jiajun; Dasari, Nagamalleswara Rao; Eckstein, Martin; Rasing, Th.; Caviglia, A. D.; et al. (Physical Review X, 2019)
Ultrafast photodoping of the Mott insulators, possessing strong correlation between electronic and magnetic degrees of freedom, holds promise for launching an ultrafast dynamics of spins which cannot be described in terms of conventional models of ultrafast magnetism. Here we study the ultrafast laser-induced dynamics of the magnetic order in a novel spin-orbit Mott insulator Sr2IrO4 featuring an uncompensated pattern of antiferromagnetic spin ordering. Using the transient magneto-optical Kerr effect sensitive to the net magnetization, we reveal that photodoping by femtosecond laser pulses with photon energy above the Mott gap launches melting of the antiferromagnetic order seen as ultrafast demagnetization with a characteristic time of 300 fs followed by a sub-10-ps recovery. Nonequilibrium dynamical mean-field theory calculations based on the single-band Hubbard model confirm that ultrafast demagnetization is primarily governed by the laser-induced generation of electron-hole pairs, although the precise simulated time dependencies are rather different from the experimentally observed ones. To describe the experimental results, here we suggest a phenomenological model which is based on Onsager's formalism and accounts for the photogenerated electron-hole pairs using the concepts of holons and doublons.
CRIS-Team WoS Importer:2019-06-04